Requirements for a Blended Learning Framework in Higher Educational Institutions in Uganda - Moreen, Kabarungi; Habinka, Annabella Ejiri; Simon, Kawuma (European Journal of Science, Innovation and Technology, 2023)
In Uganda, blended learning (BL) has emerged as a popular approach to education, particularly in response to the COVID-19 pandemic, this has forced educational institutions to adopt remote learning models. Complex adaptive and Community of inquiry frameworks have been implemented worldwide to support the adoption of BL. However, the existing blended learning frameworks (BLFs) in Uganda like any other third world country suffer from issues related to policies, training, support and infrastructure. As a solution to the above challenges, a suitable BLF for Higher Educational Institutions of Learning (HEIL) is required. However, designing a BLF requires careful consideration of a range of factors to ensure the optimal learning experience for students, thus this study aimed at exploring the requirements for designing a BLF. A cross-sectional survey was conducted in three universities in south western Uganda by the help of a pretested questionnaire which was given to 1495 participants who met the inclusion criteria and consented to participate in the study. Quantitative data was collected and analyzed using IBM SPSS-26. The results revealed that 99% of the respondents strongly agreed that there are no BLFs in their institutions hence need for designing one. However, 7.19% of the respondents were not sure whether they needed a BLF. Furthermore, 94.6% of the respondents strongly agreed that BLF to be designed should align with the objectives of their institutions as one of the requirements to be considered before designing it. Furthermore, 95.9%, 98.8% and 93.8% of the respondents strongly agreed that university policies, training and support for creation of e-content respectively should be highly considered. Therefore, basing on these findings, this research study developed a Requirement Specification Document that can be used as an input for designing a BLF that will enhance the adoption of BL in HEIL in Uganda.
Keywords: Blended Learning; Requirements; High Educational Institutions of Learning; Blended learning Frameworks